How Ebla has Changed our Perception of the Ancient Near East in the Third Millennium BC - Archi, Alfonso (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2017)
The emergence in the fourth millennium BC of the first urbanised, literate society in southern Mesopotamia coincided with the widespread distribution of the so-called ‘Uruk’ material culture along the middle Euphrates, with major settlements in Habuba Kabira North and South, the religious centre at Jebel Aruda, Tell el-Hajj, Mureybet and Sheikh Hassan. Another enclave of sites proving the Uruk presence is the region around Karkamish, on the present-day Syrian-Turkish border. Uruk-inspired pottery appears even at Arslantepe (Malatya), in period VI (Late Chalcolitic 5) (Frangipane 2010: 36).